Tradição jurídica brasileira, precedentes obrigatórios e uniformização jurisprudencial: contradição em termos ou possibilidade concreta? - ALMEIDA, Roberto de Oliveira (2018)
ABSTRACT Brazilian jurisdiction has been characterized as a unpredictable and congested function. It’s happening because of a chronicle inefficiency regarding the treatment of pending causes and the unpredictable solutions that are produced to the identical ones. To dissent is normal in the legal discourse because of its dialectical nature. But multiple decisions to equal cases violates several fundamental guarantees, such as equality, legal certainty, predictability. Regarding this matter the 2015 Procedural Law inserted in the legal order a system of binding decisions and a series of duties to the jurisdictional organs such as the necessity of maintaining a uniform, whole, stable and coherent jurisprudence. This research verifies that the 2015 Procedural Law systematics does not constitute a genuine common law precedents system because of its ahistoric, non-traditional and legal based origin. At the contrary, the stare decisis doctrine was founded on tradition. Also, its identified a lot of theoretical inconsistencies, internal incompatibilities and has its rationality and constitutionality questioned. That’s because the instruments contemplated by the new law were imported from other systems. Also the instruments are incompatible between itselves. After all the binding decisions are incompatible with the courts function such as built along the years.